Taxonomic notes on the genus Auranus (Opiliones, Laniatores, Stygnidae), with description of two new species - Colmenares, Pío A.; Porto, Willians; Tourinho, Ana Lúcia (Zootaxa, 2016)
Among the Amazonian families of harvestmen the members of Stygnidae are better known due to the recent revision of the family and efforts of specialists describing new taxa in the last few years. Species of Amazonian genus Auranus Mello-Leitão, 1941, have been collected in several inventories that were carried out in different locations of the Amazon basin. In this paper we provide a new diagnosis for Auranus, and the description of two new species: Auranus leonidas sp. nov. and Auranus xerxes sp. nov. from the Brazilian states of Roraima and Amazonas, respectively. We also offer complementary genital descriptions of Auranus hehu Pinto-da-Rocha & Tourinho 2012, Auranus parvus Mello-Leitão, 1941, and Auranus tepui Pinto-da-Rocha & Tourinho 2012. Five species are recognized in Auranus, including the two new species described in this paper. The lamina parva modified into a calyx is proposed as putative synapomorphy for the genus Auranus. Therefore, A. hoeferscovitorum, which does not possess this character, is removed from Auranus. Instead we propose for it the new combination Verrucastygnus hoeferscovitorum comb. nov. We also provide a key to the males of Auranus, and a map with the distribution for all species examined in this work.